Dysphonia and laryngeal sequelae in paracoccidioidomycosis patients: a morphological and phoniatric study - Weber, Silke Anna Theresa [UNESP]; Brasolotto, A.; Rodrigues, L.; Marcondes-Machado, J.; Padovani, Carlos Roberto [UNESP]; Carvalho, L. R.; Mendes, Rinaldo Poncio [UNESP] (Taylor & Francis Ltd, 2006)
The larynx is the third most commonly involved organ in paracoccidioidomycosis (PCM). While a few studies have evaluated laryngeal sequelae, there have not been any investigations of voice abnormalities in PCM patients. To evaluate persistent dysphonia and laryngeal lesions, we studied 15 normal subjects and 30 post-treatment PCM patients, i.e., 15 with only pulmonary and 15 with both laryngeal and pulmonary involvement. Perceptual and acoustic voice analysis were performed with all patients, while endoscopic studies were also conducted with the 15 laryngeal patients. Voice analysis showed instability by perceptual analysis (P < 0.01) in both groups, but more severe dysphonia was noted in the laryngeal group (P < 0.01). The dysponia, seen in 66.7% of these patients (dysphonia index < 7.0), was characterized by roughness and breathness. The Dr. Speech (Tiger Electronics) analysis program did not accept five voices from the laryngeal group due to the severe dysphonia. Jitter was elevated in five laryngeal lesion patients. Endoscopy showed that 80% of patients with laryngeal lesion had two or more laryngeal structures involved. Vocal fold alterations were seen in all laryngeal lesion patients, which included involvement of the arythenoids, epiglottis, and vestibular folds. This first functional study of laryngeal sequelae in PCM revealed frequent and severe dysphonia that may have important social consequences for patients.
Keywords: paracoccidioidomycosis; dysphonia; larynx; sequelae